Actinic Granuloma with Focal Segmental Glomerulosclerosis - Ruedee Phasukthaworn; Kumutnart Chanprapaph; Vasanop Vachiramon (Karger Publishers, 2016)
Actinic granuloma is an uncommon granulomatous disease, characterized by annular erythematous plaque with central clearing predominately located on sun-damaged skin. The pathogenesis is not well understood, ultraviolet radiation is recognized as precipitating factor. We report a case of a 52-year-old woman who presented with asymptomatic annular erythematous plaques on the forehead and both cheeks persisting for 2 years. The clinical presentation and histopathologic findings support the diagnosis of actinic granuloma. During that period of time, she also developed focal segmental glomerulosclerosis. The association between actinic granuloma and focal segmental glomerulosclerosis needs to be clarified by further studies.